Additional Value of Non-contrast Chest CT in the Prediction of Adverse Cardiovascular Events in Patients With Novel Coronavirus Disease 2019 (COVID-19) - Li, Shuang; Wang, Xiaojun; Hu, Hongyao; Xu, Jing; He, Jian; Yang, Wenjing; He, Bin; Liu, Yanmei; Yu, Huidan; Zhou, Quan; Zhang, Haijun; Liu, Tingting; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background Coronavirus disease 2019 (COVID-19) has outbroken in China and subsequently spread worldwide since the end of 2019. Chest CT plays an important role in the diagnosis of lung diseases, but its value in the diagnosis of cardiac injury remains unknown. Methods We enrolled 241 consecutive hospitalized patients (age 61±15 years, 115 males) with laboratory confirmed COVID-19 at Renmin Hospital of Wuhan University from January 11 to March 2, 2020. They were divided into two groups according to whether MACE occurred during the follow-up. The anteroposterior diameter of the left atrium (LAD), the length of the left ventricle (LV) and cardiothoracic ratio (CTR) were measured. The values of myocardial CT were also recorded. Results Of 241 patients, 115 patients (47.7%) had adverse cardiovascular events. Compared with no MACE, patients with MACE were more likely to have bilateral lesions (95.7% vs. 86.5%, p=0.01). In multivariable analysis, bronchial wall thickening would increase the odds of MACE by 13.42 (p =0.01). LAD+LV and CTR was the best predictor for MACE (AUC=0.88 p<0.001) with a sensitivity of 82.6% and a specificity of 80.2%. Plasma Hs-TnI levels in patients with cardiac injury showed a moderate negative correlation with minimum CT value (R2=-0.636, p < .001). Conclusions Non-contrast chest CT can be a useful modality for detection cardiac injury and provide additional value to predict MACE in COVID-19 patients.